Genetic and clinical profiles of 160 papillary thyroid cancers with lateral neck lymph node metastasis - Fang, Yiqiao; Zheng, Xun; Zou, Xiuhe; Ye, Zi; Liu, Jiaye; Lei, Jianyong; Li, Zhihui (Frontiers in Oncology, 2023)
Background Lymph node metastasis is widespread in papillary thyroid cancer (PTC). Patients are more vulnerable than those with central lymph node metastasis if they have lateral neck lymph node metastasis (LLNM). There are few researches focus on the correlation between clinical characteristics and genetic profile of PTC with LLNM. In this study, we aimed to analyze the clinical and genetic features of PTC with LLNM. Methods A total of 160 primary tumor samples derived from PTC patients with LLNM were involved. Targeted next-generation sequencing was carried out on all samples with 57 known thyroid-cancer-related genes. The associations between genomic alternations and clinical characteristics of PTC with LLNM were statistically evaluated. Results The median age of patients was 37 years, ranging from 5 to 77 years and the female/male ratio was 1.86. The most frequently altered genes in our series were BRAF mutation (68%), followed by RET fusion (17%), TERT promoter mutation (5%) and PIK3CA mutation (2%). To be noted, all PTC patients with LLNM of TERT promoter mutations appeared along with BRAF mutations (8/8) and half of them experienced a relapse. Intriguingly, we found more metastatic lymph nodes in patients with RET fusion, but there was no statistically significant difference in metastatic lymph node ratio than those with BRAF mutation or without mutation. A high rate of gene fusion (70%) was found in the pediatric population, with aggressive late-onset disease. Conclusions PTC patients with LLNM is characterized by a high rate of BRAF mutation. Due to the observed clinicopathological differences in those patients among different alterations, further prospective studies are needed to verify our results and to evaluate the most suitable treatment strategies.